Microstructure and mechanical properties of GTA-based wire arc additive manufactured AZ91D magnesium alloy - Xiaoyu Cai; Fukang Chen; Bolun Dong; Sanbao Lin; Chunli Yang (Journal of Magnesium and Alloys)
Wire arc additive manufacturing offers advantages in producing large metal structures. The current research on GTA-based wire arc additive manufacturing (GTA-WAAM) of magnesium alloys is focused on deformed magnesium alloys, mainly on the Mg-Al alloy system. However, there is little research on GTA-WAAM for casting magnesium alloy. This study investigates the microstructural characteristics and mechanical properties of AZ91D magnesium alloy (AZ91D-Mg) deposited by GTA-WAAM. Single-pass multilayer thin-walled components were successfully fabricated. The results show that equiaxed grains dominate the microstructure of the deposited samples. During the remelting process, the precipitated phases dissolve into the matrix, and they precipitate and grow from the matrix under the thermal effect of the subsequent thermal cycle. The mechanical properties in the vertical and horizontal directions are similar, showing higher overall mechanical properties than the casting parts. The average yield strength is 110.5 MPa, the ultimate tensile strength is 243.6 MPa, and the elongation is 11.7%. The overall hardness distribution in the deposited sample is relatively uniform, and the average microhardness is 59.6 HV0.2.